The Influence of Work Motivation and Self-Efficacy on Employee Performance - Misbachul Munir; Samsul Arifin (Universitas Nusantara PGRI Kediri, 2021)
Human resource management aims to realize the performance of employees who have contributed to the achievement and development of company performance. The purpose of this study was to analyze and determine the effect of work motivation and self-efficacy partially and simultaneously on employee performance. The population in this study were employees at a bakery in Mojokerto City, amounting to 42 people. The sampling technique was carried out by means of a census. The analysis technique in this study is multiple linear regression analysis with SPSS 26. The results of the study found that work motivation and self-efficacy had a significant partial and simultaneous effect on employee performance.